'If this isn't for my children, who is it for?' Exploring experiences of structural violence among migrant mothers who sell sex in Johannesburg. (9th February 2017) - Jane Walker, Rebecca Jane
Abstract : This article examines the vulnerabilities and forms of structural violence experienced by migrant mothers who sell sex.In Johannesburg, migrant sex workers face multiple vulnerabilities including abuse, discrimination, criminalisation, and many levels of violence, directed particularly at non-nationals. For migrant mothers selling sex, these vulnerabilities increase as they balance the responsibilities of providing for their dependants with the risks and challenges that selling sex entails. Drawing from semi-structured interviews with cross-border migrant women, this article explores their difficulties in accessing healthcare, in finding accommodation, widespread stigmatisation and xenophobia. The article argues that to develop a greater understanding of women who are migrants, who sell sex and who are mothers, there is a need to further explore the challenges that they face as well as the multiple roles negotiated in everyday life